Effect of traditional system of cross-ploughing on standing broadcast-sown rice (Oryza sativa) varieties under rainfed lowland situation - MOORTHY, B T S; RAO, K S (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during the wet seasons of 1990 and 1991 at Cuttack to assess the efficiency of[traditional system of cross-ploughing (beushen) in direct-seeded rice (Oryza sativa L.) for controlling weeds in 3 long-duration phoro-sensitive varieties. The varieties were ’Tulasi’ (semi-tall, plant height 111 cm), ’Gayatri’ (semi-dwarf, plant height 98.9 cm) and’ Utkalprabha’ (semi-tall, plant height 113 cm). The traditional practice of cross-ploughing supplemented with gap-tilling and hand-weeding controlled the weeds effectively (weed-control efficiency, 77.1 % at 70 days after sowing) and gave the highest yield (3.54 tonnes/ha) and benefit: cost ratio (2.18) No differential response of varieties to the practice of cross-ploughing was observed, indicating that this can be adopted in varieties of different plant types.